2015
DOI: 10.4103/0970-1591.156918
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for lymph node positivity in patients undergoing extended pelvic lymphadenectomy during robot assisted radical prostatectomy

Abstract: Introduction:Pelvic lymphadenectomy during radical prostatectomy (RP) improves staging and may provide a therapeutic benefit. However, there is no clear consensus on the selection criteria for subjecting patients to this additional procedure. With a growing adoption of robot assisted radical prostatectomy (RARP) in India, it has become imperative to study the incidence and predictive factors for lymph node involvement in our patients.Materials and Methods:From February 2010 to February 2014, 452 RARP procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The demographic and characteristics of disease are different in India. Batra et al .,[ 14 ] showed that the majority of Indian patients had higher stage prostate disease (93% patients had intermediate and high-risk D' Amico category prostate cancer).…”
Section: Discussionmentioning
confidence: 99%
“…The demographic and characteristics of disease are different in India. Batra et al .,[ 14 ] showed that the majority of Indian patients had higher stage prostate disease (93% patients had intermediate and high-risk D' Amico category prostate cancer).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have evaluated the diagnostic performance of this tracer, in lymph node staging at initial diagnosis of PCa, with ePLND as reference standard. 30 , 31 , 32 Sensitivity ranged from 61% to 82% and specificity from 84% to 95% in these studies. The sensitivity of 68 Ga-PSMA PET/CT is higher, but specificity is somewhat lower, compared to 11 C acetate PET/CT.…”
Section: Discussionmentioning
confidence: 60%
“…Another recent study by Batra et al . 30 investigated predictive factors for LN metastases in 100 patients undergoing ePLND. Variables examined in simple logistic regression analysis were PSA, Gleason score, clinical stage, D’Amico risk category and features of locally advanced disease on MRI (defined as extraprostatic extension, seminal vesicle invasion and enlarged pelvic lymph nodes).…”
Section: Discussionmentioning
confidence: 99%
“…Current research has shown a tendency to find ways to minimize the volume of PLND. Among them there is the study of the diagnostic efficiency of sentinel node biopsy (SNB) [9]. Given the anatomical features of the lymphatic drainage of the prostate, the volume of limited PLND may not include sentinel lymph nodes [12].…”
mentioning
confidence: 99%